2016
DOI: 10.3390/chemosensors4040023
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Affibody-Based Recognition Strategy for Human Epidermal Growth Factor Receptor 2 (HER2) Detection by Electrochemical Biosensors

Abstract: Abstract:In this study, we have designed and realized three simple electrochemical bioassays for the detection of the human epidermal growth factor receptor 2 (HER2) cancer biomarker using magnetic beads coupling screen-printed arrays. The different approaches were based on a sandwich format in which affibody (Af) or antibody (Ab) molecules were coupled respectively to streptavidin or protein A-modified magnetic beads. The bioreceptor-modified beads were used to capture the HER2 protein from the sample and san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Ilkhani et al [23] reported three simple magnetic bead-based approaches, combined with screen-printed arrays, for the analysis of HER2. The bioassays were based on a sandwich format in which affibody (Af) or antibody molecules were immobilized on streptavidin-or protein A-modified MBs (Strept-MBs or Prot A-MBs).…”
Section: Magnetic Immunoassaysmentioning
confidence: 99%
“…Ilkhani et al [23] reported three simple magnetic bead-based approaches, combined with screen-printed arrays, for the analysis of HER2. The bioassays were based on a sandwich format in which affibody (Af) or antibody molecules were immobilized on streptavidin-or protein A-modified MBs (Strept-MBs or Prot A-MBs).…”
Section: Magnetic Immunoassaysmentioning
confidence: 99%
“…Although in label-free assays the analysis times are shorter than in the sandwich-type assays, the time required for the electrode surface modification and subsequent incubation of the capture antibody is considerably higher. From the comparison of the analytical performances of the immunomagnetic assays [14][15][16][17][18] with the immunosensors [10,11,13,19] can be concluded that when magnetic beads are used as sensing platform, shorter linear ranges and slightly lower LODs were obtained. This indicates that the use of magnetic particles and the detection strategy optimized in this work is promising.…”
Section: Analytical Performance and Applicabilitymentioning
confidence: 99%
“…Furthermore, the use of nanomaterials, with excellent and reliable physicochemical properties, in the sensor's construction increases the electrode's surface area with a subsequent increase of sensitivity [12]. Al-Khafaji et al and Ilkhani et al used magnetic beads functionalized with Protein A to improve the affinity interaction between the biomolecules and to construct faster electrochemical bioassays [16,17]. Pre-synthesized AuNPs were grown on the MWCNT-CILE surface through electrodeposition, to form AuNP/MWCNT-CILE, which is a suitable surface for antibody attachment [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marrazza and coworkers [14] propose the use of affibodies immobilized on magnetic particles to detect, with screen printed electrodes, the human epidermal growth factor receptor 2 (HER2) which is overexpressed by breast cancer cells. De Wael et al [15] study the immobilization of aptamers on core-shell nanoparticles for improving the electrochemical detection of bacteria.…”
Section: The Special Issuementioning
confidence: 99%